2018
DOI: 10.1002/jcb.27038
|View full text |Cite
|
Sign up to set email alerts
|

miR‐627/HMGB1/NF‐κB regulatory loop modulates TGF‐β1‐induced pulmonary fibrosis

Abstract: Pulmonary fibrosis (PF) is a fibroproliferative disease that can eventually lead to fatal lung failure. It is characterized by abnormal proliferation of fibroblasts, dysregulated fibroblast differentiation to myofibroblast, and disorganized collagen and extracellular matrix production, deposition and degradation.There is still a lack of effective treatment strategies for PF. Extracellular highmobility group box protein 1 (HMGB1) induces PF through NF-κB-mediated TGF-β1 release. Herein, we first validate the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…16 We demonstrated that suppression of HMGB1/RAGE axis by verbascoside resulted in the attenuation of the EMT characteristics, including a reduction in Slug, Snail, and α-SMA with the increased E-cadherin. Also, HMGB1 was found to be a potential upstream regulator of TGF-β pathway, [11][12][13] which was a pivotal signaling cascade in EMT and metastasis. One of the recent studies has demonstrated that repression of TGF-β signaling may be effective to suppress bone metastasis in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 We demonstrated that suppression of HMGB1/RAGE axis by verbascoside resulted in the attenuation of the EMT characteristics, including a reduction in Slug, Snail, and α-SMA with the increased E-cadherin. Also, HMGB1 was found to be a potential upstream regulator of TGF-β pathway, [11][12][13] which was a pivotal signaling cascade in EMT and metastasis. One of the recent studies has demonstrated that repression of TGF-β signaling may be effective to suppress bone metastasis in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…10 On the other hand, accumulating evidence has suggested that high-mobility group box 1 (HMGB1) is a novel mediator of EMT and capable of modulating the TGF-β-induced fibrogenesis. [11][12][13] In prostate cancer, it has been found that HMGB1 was overexpressed and may serve as a promising target for prostate cancer treatment. 14,15 Currently, it has been shown that HMGB1 promoted EMT in PC3 cells via the receptor for advanced glycation end-products (RAGE)/NF-κB signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-627 is also reported to be a potential non-invasive diagnostic marker in gastric and breast cancer types (22,23). In pulmonary diseases, miR-627 is downregulated in patients with chronic obstructive pulmonary disease and targets the high-mobility group box protein 1 to inhibit its expression, thus improving transforming growth factor-β1-induced pulmonary fibrosis (24,25). The present results demonstrated the inhibitory effect of RP11-284F21.9 on the expression of miR-627-3p.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, TGF-β1 inhibits HSC apoptosis by means of autocrine and paracrine mechanisms, induces matrix protein expression, and therefore becomes one of the most important cytokines in the process of liver fibrosis[34]. Since the promoter of the TGF-β1 activating factor tissue transglutaminase gene contains a binding site for NF-κB, the synthesis of TGF-β1 is regulated by NF-κB[35,36]. Additionally, experimental studies have shown that NF-κB can amplify the liver inflammatory reaction by enhancing the expression of some factors related to HSC activation including inflammatory factors (IL-1, TNF-α, and IL-6), cell adhesion factors, and transforming growth factors, aggravating the disease[37-40].…”
Section: Discussionmentioning
confidence: 99%